Identification of pelagic fish landed by "Lampu satu" fishermen in Merauke Regency. Issue 1 (1st December 2022) - Welliken K, M A; Sunarni,; Sajriawati,; Fatima,
Abstract: This study aims to see the types of pelagic fish caught by fishermen and to see the abundance of pelagic fish species in Lampu Satu beach, Merauke Regency. This research was conducted in June-July 2020. The methods used in this study were observation and interview methods. The data analysis used was relative abundance (Kr) and Diversity Index (H'). The results of the study were 7 species of pelagic fish from 4 families. The relative abundance value in June and July was obtained, In June the most results were the Mugil dussumieri species from the Mugilidae family with a percentage value of 64% and the lowest were the Mugil cepalus and Terapon species with a percentage value of 3%. Whereas in July, the most catch was obtained from the species of Rhinomugil corsula from the Mugilidae family with a percentage value of 30% and the lowest was the Mugil strongylura species with a percentage value of 4%.